Efficacy of the selective progesterone receptor agonist Nestorone for chronic experimental autoimmune encephalomyelitis - Garay, Laura Ines (2014)
Progesterone plays a protective role in the experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis (MS). Besides spinal cord neuropathology, MS patients present a dysfunctional hippocampus. In this work we studied the therapeutic effects of the progestin Nestorone in the brain of mice with chronic EAE. Nestorone decreased clinical grade and enhanced motor behavior. In addition, it increased cell proliferation and doublecortin positive neuroblasts in the hippocampus, increased GABAergic interneurons and attenuated the number of Iba1+ microglia/macrophages, events possibly linked to enhancement of neurogenesis. Therefore, Nestorone protected against hippocampus abnormalities and improved functional outcomes of EAE mice, suggesting its potential value for MS.